(untitled) (Bangladesh Journal of Psychiatry, 2020)
The prevalence of substance use is on rising trend in the country. This two-stage nationwide multicentric community based cross sectional study was conducted by National Institute of Mental Health (NIMH), Dhaka during the period of September 2017 to July 2018 to determine the prevalence of substance use as well as to identify the proportion of users used different substances and to find out socio-demographic correlates of substance use in Bangladesh. The sample were collected by cluster sampling technique. In the first stage data were collected from 19692 respondents aged between 7 years and above in 140 clusters through face-to-face interview using semi-structured questionnaires to collect information by trained data collector. Diagnoses of substance use were made in the second stage of interview by research psychiatrists following DSM-5 diagnostic criteria of mental disorders. Descriptive and inferential statistics of the collected data was done using standard statistical parameters. SPSS programme (Version 23) was used to summarize and to analyze the data. The results showed that, the prevalence of substance use was found as 3.3% among the population 18 years and above. Prevalence of substance use was 4.8% in male and 0.6% in female. Most frequently used substances include cannabis in (42.7%), alcohol in 27.5%, amphetamine (yaba) in 15.2%, opioid in 5.3% and sleeping pills in 3.4% users. Among professions of substance users 6.7% were labors, 5.7% unemployed, 4.3% business men, 3.8% farmers and 3.5% service holders. Extremes of social classes were found as increased users of substances such as people with low income 3.2% and people with high income 3.8% using as against 2.6% in middle income group. The data of this community survey will be used for planning of mental health services in Bangladesh. Bang J Psychiatry June 2018; 32(1): 1-8